Host Plant Catalog of Aphids: Palaearctic Region - Holman, Jaroslav (Springer, 2017)
The Aphids and their Host Plants -- Host Plant Genera, Families and Major Taxa(Bryophyta, Pteridophyta, Gymnospermae, Dicotyledonae and Monocotyledonae) -- The Plants and their Aphids -- References